(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2018)
In contemporary culture, death is mostly understood as a concept which is completely alternative to life. Therefore, legal culture interprets death as a deprivation of a protected interest. In this context, when the loss of the protected interest “life” depends on unlawful conduct of a third party it can become, for certain authors, a case of non-contractual liability. The debate around the issue shows that this cultural setting is simply the result of naturalism and the philosophical idea of science that is connected to it. However, in this manner, that is, by adhering to a philosophical theory, legal culture loses its secular nature.